Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.echo.2014.04.024
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Procedural Sedation on Diagnostic Errors in Pediatric Echocardiography

Abstract: Background Infants and young children frequently have difficulty remaining still for an echocardiogram, potentially leading to poor study quality, increasing the likelihood of diagnostic errors. Sedation is believed to improve echocardiography quality; however, its effectiveness has not been demonstrated. We hypothesized that sedation would improve study quality and reduce diagnostic errors. Methods We examined outpatient echocardiograms in children ≤ 36 months from January 2008 – June 2009. We collected var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Distraction techniques, such as video viewing can be successful to obtain complete echocardiographic studies(9) but more recent data have shown that sedation results in higher quality studies and reduces the risk of preventable diagnostic errors, particularly in patients with moderate or high complexity disease(1). It is our general policy to sedate patients needing complete echocardiograms between 1 month and 2 years of age and use distraction techniques above this age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distraction techniques, such as video viewing can be successful to obtain complete echocardiographic studies(9) but more recent data have shown that sedation results in higher quality studies and reduces the risk of preventable diagnostic errors, particularly in patients with moderate or high complexity disease(1). It is our general policy to sedate patients needing complete echocardiograms between 1 month and 2 years of age and use distraction techniques above this age.…”
Section: Discussionmentioning
confidence: 99%
“…Use of sedation in this age group improves image quality and reduces diagnostic errors, particularly in those with more complex disease(1). Chloral hydrate has been the medication of choice for many pediatric echo labs due to its low cost, oral availability (100mg/mL solution) and safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, echocardiography is quick, less expensive, and widely available. Not infrequently, sedation must be administered to minimize diagnostic errors, 18 although in most cases there is no need for it even if small children are investigated. Established twodimensional techniques are lacking in accuracy to determine LVM because they rely on geometric assumptions and use equations that cannot entirely compensate for the individual shape of a chamber.…”
mentioning
confidence: 99%
“…Predictor variables collected included the following: patient weight, age, KD criteria fulfilled, IVIG administration prior to TTE, recent antipyretic (ibuprofen, acetaminophen, aspirin [ASA]) use within 6 hours prior to initial TTE, fever within 1 hour of TTE, number of days since start of KD fever, and inflammatory laboratory markers. The age and weight variables were converted into binary variables (≤ or > 2.0 years and ≤ or > 10 kg) as has been done in similar literature and for ease‐of‐use in any resulting management criteria. KD type by criteria fulfilled (Complete, Incomplete) were assigned in accordance with the American Heart Association (AHA)‐endorsed KD diagnostic guidelines at the time of the initial KD TTE .…”
Section: Methodsmentioning
confidence: 99%